Main Characteristics of the Baltic Countries Political Development and their Economic Consequences - Vladimir A. Shamakhov; Natalia V. Eremina; Nikolay M. Mezhevichc (Управленческое консультирование)
Studying of social and economic processes in the former Soviet Union has not only the academic value. Estimation of transformation results in economy and policy of Russia is possible only in comparison with the states anyway moving in the same direction. The transformational model of Republic of Belarus as the instruction on other model of development, under the same starting conditions, is of considerable interest to us. Practice of social and economic development of the Baltic Countries has however not smaller value for us: Estonia, Latvia, and Lithuania. Their progress during 1991-2007 and even more obvious modern problems is for us a peculiar anti-index of reforming, a compass which arrow is directed to the south. Having proclaimed democracy and the free market how the Baltic Countries lost both the first, and the second? Why it occurred? The answer is offered in this article.